Phosphate Fertilizer in Soybean-Wheat Cropping System Under No-Till Management - Moreira, Adônis; Moraes, Larissa A. C.; Petineli, Rafael (Frontiers in Sustainable Food Systems, 2020)
Improvements in soybean (Glycine max [L.] Merrill) and wheat (Triticum aestivum L.) yields in cropping systems under no-till management (NTM) in the subtropics have been obtained through advances in phosphorus (P) utilization, cultivar selection, and planting and harvesting strategies. This fact, along with the P application in band application in consolidated planting, has resulted in adequate P utilization efficiency and small depleted soil P levels. The aim of this study was to evaluate the efficiency of P2O5 rates and application methods in soybean-wheat cropping under NTM during two growing seasons (2014–2016) in a Typical Eutrorthox. Four P2O5 rates (0, 30, 60, and 120 kg ha−1) of triple superphosphate (45% P2O5) were applied using two application methods (broadcast and band application at sowing) before the soybean and wheat crops were cultivated. Both P application methods resulted in a significant yield response to P2O5 rates for the soybean and wheat crops. Under NTM, broadcast P2O5 application was more effective than band application in soybean, and maximum grain yields were obtained with 129.3 and 88.1 kg P2O5 ha−1, respectively. Maximum wheat grain yields were obtained with 91.8 and 99.7 kg P2O5 ha−1 for broadcast and band application, respectively. Except for total P in leaves, nutrient uptake and yield components were not affected by the P application methods and rates. The results suggested that in soils with adequate available P levels of >15 mg kg−1 (Mehlich 1 extractant), the grain yield is equivalent or superior with broadcast P application as compared with band application for both soybean and wheat crops when cultivated in a Typical Eutrorthox under subtropical conditions. However, broadcast application is considered more effective for large areas of grain cultivation, where it is necessary to sow crops uniformly within the shortest possible time.